The Effect of Hypnotherapy on Students’ Anxiety Levels and Learning Motivation in Mathematics at SMPN 252 Jakarta - Noviyanti, Adhe; Endarti, Ajeng Tias; Djaali , Nur Asniati (Jurnal Kesehatan Masyarakat Perkotaan, 2026)
Mathematics anxiety and low learning motivation are psychological factors that may hinder students’ academic achievement. Emotional-based learning approaches are needed to create a more effective and humanistic learning process. This study aimed to analyze the effect of hypnotherapy on students’ anxiety levels and learning motivation in mathematics at SMPN 252 Jakarta. A quantitative method with a quasi-experimental pretest–posttest control group design was employed. The sample consisted of 52 students divided into an intervention group (26 students) and a control group (26 students). Data were collected through questionnaires administered before and after the intervention and analyzed using the Wilcoxon test and paired sample test. The results showed a significant decrease in anxiety levels in the intervention group from 9.346 to 5.250 (p = 0.000) and a significant increase in learning motivation from 54.827 to 76.173 (p = 0.000). The control group showed no significant changes in anxiety (p = 0.180) or motivation (p = 0.745). It can be concluded that hypnotherapy is an effective psychoeducational intervention to reduce mathematics anxiety and enhance students’ learning motivation.